Personal Selling Analysis To Increase Sales At Mari Mampir Vegetarian - susanto; Tampubolon, Mangihut (Journal Boas : Business, Economics, Accounting And Management, 2023)
This research discusses the implementation of Personal Selling, by parties here to stop by in an effort to increase sales. The problems taken are how to implement Personal Selling, as well as the obstacles and efforts to increase sales. The problems taken are how to apply personal selling, as well as the obstacles and constraints experienced in implementing personal selling. This study aims to find out the strategy used by let's stop by, namely to know and understand product knowledge, and understand the hearts of consumers first. The media used in implementing personal selling strategies are door to door media, telephone media, social media. This research method is descriptive research with a qualitative approach. Data collection was carried out by observation and interview techniques. Researchers use source triangulation to check the validity of research data. Data analysis in this study uses 3 components, namely data reduction, data presentation, and drawing conclusions. The results of the study show that Let's Stop Vegetarian applies the dimensions of Relationship, Value, Trust, Empathy and their indicators.